A 5G Vehicle-to-Everything Ecosystem with Internet of Vehicles based Approaches - Storck, Carlos R.; Duarte-Figueiredo, Fátima (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2021)
The Fifth Generation (5G) cellular network is a good infrastructure option to connect vehicles through the Cellular-based Vehicle-to-Everything (C-V2X) technology. C-V2X aims to provide drivers comfort, road safety, autonomous steering for reliable connections and Advanced Driver Assistance Systems (ADAS). To 5G effectively provide C-V2X communications, there are many questions to answer and many problems to solve. One of them is the absence of an architecture that absorbs and characterizes the vehicles as special things in the Internet. The connectivity continuity guarantees after a handover is a huge problem because the vehicles have high mobility. It raises their handover occurrences as well as failed and unnecessary handovers. The thesis titled "A 5G Vehicle-to-Everything Ecosystem with Internet of Vehicles based Approaches" goals were the characterization of the IoV (Internet of Vehicles) the architecture supported by a 5G network on C-V2X communications, proposition of a 5G V2X ecosystem, the presentation of an user-centered Virtual Cells (V-Cells) selection probabilistic approach, a vehicular handover decision solution based on complex network metrics for 5G Ultra-Dense Network (UDN) and the validation of a structured model as a new 5G service provider facilitator. This thesis proposal and contributions include FiVH (5G Vehicular Handover) a solution that does the virtual cells selection and conformation and deals with the frequent handovers to provide many IoV services, such as on board video entertainment applications. The C-V2X applications can be efficiently supported by the 5G vehicle-to-everything ecosystem IoV communications.